A prospective national study of acute fatty liver of pregnancy in the UK. Issue 7 (10th March 2008) - Knight, M; Nelson-Piercy, C; Kurinczuk, J J; Spark, P; Brocklehurst, P
Abstract : Objectives: To identify a national, population-based cohort of women with acute fatty liver of pregnancy (AFLP), to evaluate proposed diagnostic criteria and to document accurately the incidence, management and outcomes of the condition. Subjects and methods: This was a population-based descriptive study using the UK Obstetric Surveillance System, carried out in all 229 hospitals with consultant-led maternity units in the UK. The participants comprised 57 women in the UK diagnosed with AFLP between February 2005 and August 2006 in an estimated cohort of 1 132 964 maternities (women delivering). Results: The estimated incidence of AFLP was 5.0 cases per 100 000 maternities (95% CI 3.8 to 6.5 per 100 000). Fifty-five cases (90%) were confirmed by diagnostic criteria and clinical assessment, two (3%) by clinical assessment alone, representing 97% agreement (kappa statistic = 0.78). 18% of women had twin pregnancies and 20% were underweight (body mass index (BMI) <20). 60% of women were admitted to intensive care and 15% to a specialist liver unit. One woman received a liver transplant. One woman died (case fatality rate 1.8%, 95% CI 0% to 9.4%). There were seven deaths among 67 infants (perinatal mortality rate 104 per 1000 births, 95% CI 43 to 203). Conclusions: The largest population-based cohort of women with AFLP to date has been identified. Diagnostic criteria previously proposed agree substantially with clinical diagnosis. The incidence estimate from this study is lower than documented by earlier hospital-based studies, but maternal and neonatal outcomes are better than previously reported, possibly related to improved ascertainment. Women with twin pregnancies appear to be at higher risk, but further studies are needed to investigate the risk associated with low BMI.